A SPEAK CUSTOM: HOW THE MARKOBAR TRADITIONAL CEREMONY AFFECTS ELEMENTARY SCHOOL TEACHER EDUCATION STUDENTS' SPEAKING SKILL - Suci Perwita Sari (PIONIR: JURNAL PENDIDIKAN, 2025)
Speaking is one way to convey messages and mandates verbally. In this process, the speaker acts as an encoder, using language codes to send messages and mandates. These messages are then received by the listener who serves as a decoder, breaking down the codes conveyed to provide meaning and interpretation. This communication process occurs interactively, with speakers and listeners alternating roles, creating a dynamic reciprocal communication flow. The goal of this research is to ascertain how the application of the Markobar custom be learning strategy impacts the speaking abilities of fifth grade Elementary School Teacher Education. Markobar, an oral tradition from the Mandailing culture, was transformed into a learning strategy that focuses on delivering messages in turns, with politeness and structure. A quantitative approach with an experimental design was employed in this study. Class A, the experimental group, received a learning intervention using Markobar, and Class B, the control group, utilized the lecture method. The data collcetive involved a speaking skills observation sheet that comprised indicators of expression, fluency, sentence structure, word choice, and content accuracy. The outcomes of the tests for normality and homogeneity indicated that the data followed a normal distribution and was homogeneous. The significance value for Hypothesis was 0.000 < 0.05. it means, the use of Markobar significantly affected the enhancement of students' speaking skills. This study's findings suggest that the Markobar strategy is effective for enhancing students' speaking skills and serves as a significant initiative for local culture preservation in education. Deviations from expected outcomes—such as persistent student passivity—can be attributed to heterogeneous student backgrounds, where not all comprehend Mandailing language/terms, coupled with limited rehearsal time for markobar exercises, preventing universal achievement of advanced proficiency levels. Keywords: Speak custom, Markorbar traditional ceremony, Speaking skill